GE_GERICHTE P/10643/2021 vom 18. Juni 2024 - GE Cour de justice (2024)
IN DUBIO PRO REO;VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;INJURE;CONTRAINTE(DROIT PÉNAL) | CP.123.al3.ch2; CP.126.al1; CP.181; CP.177; CP.219